Efetue as operações : (- 5x). (x+2x - 3) alguém pode me ajudar por favor?!
Soluções para a tarefa
Respondido por
0
Olá Brusa
(-5x)*(x + 3x - 3)
(-5x)*(4x - 3) = -20x² + 15x
.
(-5x)*(x + 3x - 3)
(-5x)*(4x - 3) = -20x² + 15x
.
Respondido por
0
(-5x) . (x +2x -3)
-5x² -10x² +15x
-15x² +15x = 0
Δ = 225 + 0
Δ = 225
x = -15 +-√225/-30
x´= -15 +15 /-30 = 0
x´´ = -15 -15/-30 = 1 ok
-5x² -10x² +15x
-15x² +15x = 0
Δ = 225 + 0
Δ = 225
x = -15 +-√225/-30
x´= -15 +15 /-30 = 0
x´´ = -15 -15/-30 = 1 ok
Perguntas interessantes